Identifikasi Tingkat Kepuasan Kerja Karyawan Panen Kelapa Sawit (Elaeis Guineensis Jacq.) Terhadap Sistem Premi Panen Yang Diterapkan Di PTPN Ii Unit Kebun Tanjung Garbus - Walmadri Walmadri; M.Riyan M.Riyan; Delyana R.Pulungan; Fastabiqul Khairad (CULTIVATE: Journal of Agriculture Science, 2024)
The aim of this research is to identify how the harvest premium system applies at PT. Perkebunan Nusantara II Tanjung Garbus Gardens. Second, to identify the level of job satisfaction of harvest employees at PT. Perkebunan Nusantara II Tanjung Garbus Gardens. This research is located at PT. Pekebunan Nusantara II Tanjung Garbus Gardens. Data collection was carried out by conducting observations, interviews and documentation. The data source used in this research is qualitative descriptive analysis using a Likert scale and correlation analysis. Based on the results of research that has been carried out, the employee satisfaction index value for the premiums provided by the company is 52.38% very satisfied and 47.62% satisfied. According to the satisfaction index criteria according to Rangkuti, it can be concluded that employees are quite satisfied with the premiums provided by the company.